Studi Fenomenologis: Menguak Partisipasi Masyarakat Dalam Proses Penyusunan APBD - Sopanah Sopanah (Jurnal Akuntansi dan Auditing Indonesia, 2010)
The main aim of this research is to describe the phenomenon of society participation on local government budgeting process at Malang City. Hence, this research is developed based on interpretive paradigm. The approach and technique of phenomenology analysis is used to explore comprehensive meaning of participation phenomenon on local government budgeting process. The result of the research on the phenomenon of society participation on local government budgeting process shows that it is in accordance to the mechanism arranged in the Act No 25 2004. Other result shows that the phenomenon of society participation on local government budgeting process is still Utopic because of limited socialization to the public so that only certain parties could access information and propose program. Meanwhile, when the mechanism of Musrenbangkot is desisted, there will be problem in local government budgeting process which will lead also to politics problem.Keywords: Participation, local government budgeting process, phenomenology